Hydrothermal and thermal treatment of natural clinoptilolite zeolite from Bigadi‡, Turkey: An experimental study - Akkoca, Dicle Bal; Yilgin, Melek; Ural, Melek; Akcin, Hasan; Mergen, Ayhan (Maik Nauka/Interperiodica/Springer, 2013)
The clinoptilolite rich zeolite from Bigadi double dagger which was formed from alteration of volcanic glass were treated with acidic (HCl, H3BO3, H3PO4), alkaline (KOH, NaOH) solutions. Hydrothermally treated and untreated samples were heat treated at 400, 550 and 700A degrees C. XRD, ICP-MS and N-2 gas adsorption were used for physicochemical characterization of zeolites. Considering the Si/Al > 4 and Na+K/Ca+Mg < 1 ratios, zeolite sample is included to earth alkali clinoptilolite class (Heu II) which is also revealed by thermal treatments. Since zeolite structure contains low alkalies it was at collapsed 550A degrees C. The removal of oxide elements efficiency of acids and alkalies were in the order of HCl > H3PO4 > HBO3 > KOH > NaOH. XRD analysis indicated that the structure of zeolite was not altered with acids and alkali treatments. The structure of zeolite treated with HCl and other acids started to deform at 400 and 550A degrees C respectively. In treatment with HCl, Si/Al ratio increases with significant a decrease in K content which resulted in a decrease in the heat stability of zeolite. No change was observed in the structure and thermal stability of clinoptilolite after alkali treatments. The fact that although significant amount of Na is removed with H3BO3 acid and Na is increased with NaOH but the thermal stability remains the same indicates that Na cation is not an important parameter as much as K. HCl and H3PO4 acid treatments increased the surface area depending on the dissolution of amorphous material and H3PO4 was found to be more effective. However, the total pore size decreased due to formation of new micropores.
Keywords: clinoptilolite; dealumination; alkaline; acid; thermal treatment; Bigadic